Enhancement of knee beam-column joint performance using hybrid fiber-reinforced concrete - S. Zainal Abidin, Sheikh Mohd Iqbal (2020)
The knee beam-column joint is the weakest beam-column configuration in a Reinforced Concrete (RC) structure, particularly when subjected to earthquake vibrations. Current structural design codes dictate the use of high amounts of steel reinforcements in the frame joint to manage the large strain demand in seismic-prone regions. However, this resulted in congestion of steel reinforcements in the limited joint-area and produced numerous construction complications in RC structures. Fibers are known to improve the mode of failure of concrete from brittle to ductile as a result of their crack fiber-bridging effect. Hence, an attempt has been made in this study to improve the performance of the joint region by developing Hybrid Fiber Reinforced Concrete (HyFRC) from the combination of multiple synthetic fibers. For this purpose, sixteen fiber-combinations with different fiber parameters ranging from size, length, volume fraction, bonding power, materials, and form are designed. These parameters were evaluated under flexural residual-strength tests to analyze its hybridization synergistic effect in improving the Average Residual Strength (ARS) of concrete. The results showed positive fiber synergy with an improvement of the ARS from the controlled specimens by 6.12% for the Ferro-Ultra hybrid, 10.2% for the Ferro-Super hybrid, 7.48% for the Ferro-Econo hybrid, and 20.41% for the Ferro- Nylo hybrid. The developed hybrids were also tested under direct shear, resulting in improved shear strength of controlled specimens by Ferro-Ultra (32%), Ferro-Super (24%), Ferro-Econo (44%), and Ferro-Nylo (24%) whilst producing positive fiber synergy under direct shear at large crack deformations. Subsequently, experimental testing in uniaxial compression and tension were conducted to evaluate the behavior of the HyFRC with added High Range Water Reducing Admixture (HRWRA). Constitutive models for each of the materials are formulated to be used as analytical models in numerical analyses. The acquired data are then used to formulate mathematical equations, governing the stress-strain behavior of the proposed HyFRC materials to measure the accuracy of the proposed models. The experimental testing indicated that the Ferro-Ferro mix-combination improved the performance of concrete in the elastic stage while the Ferro-Ultra combination has the highest compressive strain surplus in the plastic stage. In tension, the Ferro-Ferro mix displayed the highest elastic behavior improvement while the Ferro-Ultra designs proved superior in the plastic range, providing additional toughness to conventional concrete. Consequently, six Knee Joint (KJ) specimens were cast using five developed HyFRC materials and one control specimen to be experimentally tested under lateral cyclic loading. The results indicated significant improvements for the HyFRC KJ specimens in energy dissipation capacity, stiffness degradation rate, displacement ductility toughness, steel reinforcement strain, and hysteretic behavior. Six Finite Element (FE) KJ models were then developed using the HyFRC analytical models for verification against the results from the experimental testing. The accuracy of the proposed FE models resulted in an average percentage difference of 25.89% for peak load, 3.45% for peak load displacement, and 0.18% for maximum displacements from the experimental data. This research concluded that the developed HyFRC materials are beneficial in providing cost-efficient alternatives to RC KJ structures in areas with low to moderate levels of seismic risks.